Strategi Manajemen Risiko Produksi Padi Varietas Ciherang dan Inpari 32 - Hasanah, Uswatun; Rahman, Rena Y; Aji, Joni M. M; Utami, Ratih A (JURNAL BUDIDAYA PERTANIAN, 2025)
Rice is a food crop that plays an important role in meeting the food needs of the community. Rice production in Tanggul Wetan Village has decreased for three consecutive years from 2020 to 2022. One of the efforts to increase rice production is to use superior varieties. The majority of farmers in Tanggul Wetan Village use Ciherang and Inpari 32 varieties of rice. However, the use of superior varieties is not entirely an effort to increase production. There are other problems that result in production risks. The purpose of this study was to find out the sources of risk, risk magnitude, and risk management strategies for rice production of Ciherang and Inpari 32 varieties. This research method used descriptive, analytical, and comparative methods through primary and secondary data collection. Based on the results of the study, the sources of production risk consisted of weather changes, pest and disease attacks, wind attacks, and inappropriate use of chemical pesticides. The coefficient of variation in the production risk of Inpari 32 rice variety was 0.20, which was lower than that of Ciherang rice variety of 0.30. Risk management strategies consisted of preventive and mitigation strategies. The use of this strategy was based on the average values of the probability and risk impact of rice production of Ciherang and Inpari 32 varieties, which were 2.5% and Rp 2,299,736. If it is more than this value, then the probability and impact of production risk is large. So, it is overcome by using preventive and mitigation strategies.